1993
DOI: 10.1021/ma00057a034
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of elastic and plastic response in the glassy polycarbonate of 4,4'-isopropylidenediphenol

Abstract: The previously determined molecular structure model of the dense, glassy polycarbonate of 4,4'-isopropylidenediphenol ("Bisphenol A polycarbonate" (PC)) has been used in conjunction with the structure-probing techniques of Theodorou and Suter and those of Mott et al. developed for atactic polypropylene (PP) to determine the small-strain elastic constants and study the mechanisms of large-strain plastic deformation of PC. The calculated elastic moduli of the microstructures all fall above the experimentally rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 9 publications
6
55
0
1
Order By: Relevance
“…[14][15][16][17] More chemically realistic MD simulations of polymers have been carried out on amorphous polyethylene ͑PE͒, [18][19][20][21][22][23] PS, [24][25][26][27] and PC. 24,[26][27][28] Also other simulation techniques are applied to study the deformation of polymers, such as Monte Carlo algorithms or variants of energyminimization methods for PE-alike, 29 polypropylene, 30,31 poly͑oxypropylene͒, 32 PC, [33][34][35] and PE. 36,37 As the simulation studies are limited to only small time and length scales, numerical agreement is often only possible by means of extrapolation over orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] More chemically realistic MD simulations of polymers have been carried out on amorphous polyethylene ͑PE͒, [18][19][20][21][22][23] PS, [24][25][26][27] and PC. 24,[26][27][28] Also other simulation techniques are applied to study the deformation of polymers, such as Monte Carlo algorithms or variants of energyminimization methods for PE-alike, 29 polypropylene, 30,31 poly͑oxypropylene͒, 32 PC, [33][34][35] and PE. 36,37 As the simulation studies are limited to only small time and length scales, numerical agreement is often only possible by means of extrapolation over orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 to 30 years, many studies have been devoted to the computer aided simulation of plasticity in glassy polymers (see, for example, [28][29][30][31][32][33][34][35][36][37]). In most publications, the method of molecular dynamics has been used to study the conformational rearrangements in polymer chains and variations in the rates of such rearrangements under the action of an external force, the orientation of chain segments, the volume changes in elementary deformation events [31,[33][34][35][37][38][39], and some other problems associ ated with chain behavior.…”
Section: This Work Was Supported By the Russian Foundation For Basicmentioning
confidence: 99%
“…In most publications, the method of molecular dynamics has been used to study the conformational rearrangements in polymer chains and variations in the rates of such rearrangements under the action of an external force, the orientation of chain segments, the volume changes in elementary deformation events [31,[33][34][35][37][38][39], and some other problems associ ated with chain behavior. However, in all the above cited publications, growth in the potential energy of a polymer glass during its deformation has been neglected, while structures responsible for this growth have not been identified.…”
Section: This Work Was Supported By the Russian Foundation For Basicmentioning
confidence: 99%
“…Before a discussion of these results, a brief review on toughening mechanisms of typical polycarbonate with high M W and high impact strength (961 J / m ) may be in order. The high impact strength was variously attributed to shear yielding from the notch tip (2), compressive stresses on the surface (12), a correlated conformational interchange between two neighboring carbonate units (81, and secondary dynamic-mechanical relaxations (3-5, lo), and unique features of molecular structure (13,14).…”
Section: Pcmentioning
confidence: 99%
“…Moet et al (15) reported that shear yielding first takes place in a region of stress-concentration localized in a poorly packed region between regions of higher packing density. According to Hutnik et al (13). the shear yielding involves a cooperative movement of many chain segments, and rearrangements in the carbonate and isopropylidene groups are more important for the total strain than rotation of phenylene rings on the average.…”
Section: Pcmentioning
confidence: 99%